Guest Editor Note - MADRID, Nuria Sánches (Faculdade de Filosofia e Ciências, 2021)
As guest editor of this special issue of the journal Estudos Kantianos, I am honored to introduce the contributions gathered under the general title Kant and the empirical sciences. This monographic number two of the second issue of EK contains twelve articles, writtenby an outstanding international group of Kant scholars who have extensive experience on the questions addressed by the issue, published in five languages (English, Spanish, German, French and Portuguese), meeting the multilingual scope of the journal. The original idea of the monographic issue was to discuss whether Kant’s firm reduction of science, according to the proper sense of this term, to the condition of apodictic certainty could exhaust his concern withthe methodical grounding of science and scientificity. The following excerpt of Metaphysical Foundations of Natural Science (1786) displays neatly Kant’s point of view about science as a product of reason: “Only that whose certainty is apodictic can be called science properly; cognition that can contain merely empirical certainty is only improperly called science” (MAN, AA 04: 468). However, an earlier Kant’s work aiming at defending the Critique of Pure Reason against its early misunderstandings, Prolegomena to Any Future Metaphysics (1783), points out that all empirical research could be subordinated to the legislation of reason, which therefore will shed some doubts on the legitimacy of the preceding severe categorical statement. Kant formulates this suggestion as follows in the Prolegomena (AA 04: 364): “whether or notexperience is in this way mediately subordinate to the legislation of reason may be discussed by those who desire to trace the nature of reason even beyond its use in metaphysics, into the general principles of a history of nature; I have represented this task as important, butnot attempted its solution, in the book itself ”. This excerpt encourages the reader to extend the study about the legislative scope of reason beyond the field covered by metaphysics, i.e. descending to the humble bathos where the empirical sciences are cultivated. All the articles of this monographic number attempt to cast light on such a valuable and daunting task that Kantleft without an ultimate solution.